Food tourism : a netnographic study about online engagement on food tourism communities and what to look for as a business owner - Lobato, Luís Maria Fernandes Guimarães (2019)
Food tourism is becoming a relevant and developing trend in the industry of tourism. Consumers nowadays travel in order to explore and to get acquainted with cultures and realities they haven’t experienced. A substantial part of this discovery is played by food. This cultural feature is one of the strongest and most representative, it has been passed on from generation to generation to, ultimately, culminate on what it is today. Considering this trend, existing academic research about food tourism with the target of understanding consumers’ engagement has been conceived but is limited. Therefore, by using a qualitative method of netnography, the present thesis aims to understand users’ engagement in the online food tourism community. Results show the emergence of three themes that can be related to online food tourism communities. The most evident is online leadership demonstrated by the tight relationship between the leader and followers of the community. Secondly, knowledge is a theme due to the continuous exchange of food tourism expertise within the communities. Lastly, food tourism comes hand in hand with the development of emotions and the influence of behaviours, and thus the last theme to be considered is consequences. To conclude, implications include how food tourism business owners should advertise their food experiences, how they could collect valuable insights about their target audience and why opinion leaders shouldn’t be ignored.